EFFECT OF 'BRUSH YOUR TEETH' SONG ON DENTAL AND ORAL HEALTH OF DOWN SYNDROME CHILDREN - Emanuela Marchellina; Galuh Dwinta Sari; Renie Kumala Dewi; Aulia Azizah; Rahmad Arifin (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Down syndrome children are a group of children with special needs caused by abnormalities in chromosomes that result in loss of skills and brain function. Songs are innovative health promotion media, songs can help children with Down syndrome increase motivation, concentration, perceptual abilities, as well as retention and memory skills including oral health behavior. Objective: Knowing the effect of using the song "SIKAT GIGIMU: Our Beautiful Smile with Healthy Teeth" on improving the oral health behavior of children with Down syndrome. Method: Using quasi-experimental research design with one group pre and posttest method. Results: Mann Whitney test obtained a significance value of 0.000 <0.05, meaning that there is an effect of using the song "SIKAT GIGIMU: Our Beautiful Smile with Healthy Teeth"  on improving the oral health behavior of children with Down syndrome. Conclusion: The song "SIKAT GIGIMU: Our Beautiful Smile with Healthy Teeth" has an effect on improving the oral health behavior of children with Down syndrome. Keywords: down syndrome, oral health behavior, songs